Dependence Between Foreign Trade Performance and Exchange Rate Volatility: Panel ARDL Approach (2023)
The purpose of this study is to analyse the influence of exchange rate shocks on foreign trade (exports and imports) of fifteen economies within the ECOWAS sub region. To accomplish the goal of this paper, Autoregressive Distributed Lag (ARDL) procedure was employed to investigate the impact volatility in the exchange rate market has on foreign trade in both long- and short-term with data between 1980 and 2020. To compute volatility, it relied on the GARCH (1, 1) model which predicted the conditional variances as proxy for volatility. Our empirical results are distinguished into export model and import model, and reveal that volatility in exchange rate influence foreign trade performance (exports and imports) negatively in the short run, though statistically insignificant. The impact however becomes positive in the long run, and statistically significant for the two models. These results signpost that while the volatilities in foreign exchange market appear to deteriorate the international trade of these economies in the short-term, it substantially and significantly causes its improvement in the long-term. Hence, our results validate the J curve effect in the case of these ECOWAS economies. Policy implication from the findings suggests that to develop a robust international trade and ultimate economic growth, it is recommended that policymakers of these economies maintain a short-term stability in their foreign currency markets by way of adopting some intervention measures.